The Current Situation and Problems of Teachers’ professional Development from an International Perspective and Its Enlightenment to China: based on the results of TALIS 2018 - He, Pengcheng (Pacific International Journal, 2022)
The OECD released a survey report on the global professional development of teachers in June 2019. Through the analysis of the survey report and data information, it is found that the participation of international teachers’ professional development is very high, and the content of professional development is diverse. The ways of international teachers’ professional development mainly focus on the improvement of discipline knowledge and discipline teaching ability. However, international teachers also face problems such as the conflict between work and professional development, insufficient policy support and so on. The Enlightenment of the above research findings to the professional development of Chinese teachers are: paying attention to the needs of teachers, providing diversified development methods, providing on-site training, providing policy support, and improving the incentive mechanism